2020
DOI: 10.48550/arxiv.2006.10891
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the key role of oxygen vacancies electromigration in the memristive response of ferroelectric devices

C. Ferreyra,
M. Rengifo,
M. J. Sánchez
et al.

Abstract: Ferroelectric memristors are intensively studied due to their potential implementation in data storage and processing devices. In this work we show that the memristive behavior of metal/ferroelectric oxide/metal devices relies on the competition of two effects: the modulation of metal/ferroelectric interface barriers by the switchable ferroelectric polarization and the electromigration of oxygen vacancies, with the depolarizing field playing a fundamental role in the latter. We simulate our experimental result… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Here we report operando atomic scale electron microscopy investigations of the behavior of LSMO/HZO/LSMO capacitor stacks grown on conducting (Nb-doped) STO substrate under electric field (see materials and methods in SI). LSMO is a standard choice of bottom electrode in complex oxide devices (23)(24)(25)(26)31) and, thus, the findings reported here are relevant for understanding a wider class of devices. In situ biasing measurements were performed while employing at the same time two scanning transmission electron microscopy (STEM) imaging modes: high-angle annular dark-field (HAADF) STEM and integrated differential phase contrast (iDPC) STEM.…”
Section: Main Textmentioning
confidence: 83%
See 1 more Smart Citation
“…Here we report operando atomic scale electron microscopy investigations of the behavior of LSMO/HZO/LSMO capacitor stacks grown on conducting (Nb-doped) STO substrate under electric field (see materials and methods in SI). LSMO is a standard choice of bottom electrode in complex oxide devices (23)(24)(25)(26)31) and, thus, the findings reported here are relevant for understanding a wider class of devices. In situ biasing measurements were performed while employing at the same time two scanning transmission electron microscopy (STEM) imaging modes: high-angle annular dark-field (HAADF) STEM and integrated differential phase contrast (iDPC) STEM.…”
Section: Main Textmentioning
confidence: 83%
“…More generally, in devices of thin-film ferroelectric oxides such as tunnel junctions, both V ̈o migration and polarization switching lead to memristive hysteresis (22)(23)(24)(25)(26)(27). Understanding whether these effects are synergetic or independent is crucial to achieve device control, and is a topic of active research (29)(30)(31)(32)(33). In tunnel junctions of HZO thin-films on LSMO buffered SrTiO3 (STO), Wei et al (22) observed a divergence of the tunnel electro-resistance (TER) from 100% to 10 6 %, upon device cycling, which was explained as a possible transition from polarization switching to V ̈o migration assisted switching, suggesting the independence of the two mechanisms.…”
Section: Main Textmentioning
confidence: 99%